Facial profile based evaluation of gingival zenith position in maxillary central incisors among Saudi, Indian & Bangladeshi population - Kiran Kumar Ganji; Mohammad Khursheed Alam; Ashraf Farhan Alanazi; Mohanad Aldahali (Elsevier, 2018)
Background: Recently quantitative evaluation of gingival zenith position was evaluated in different facial forms suggesting clinicians may need to evaluate patients facial form and then decide to distalise the Gingival Zenith position in relation to Vertical Bisected Midline (VBM). The aim of the study was to quantitatively evaluate the gingival zenith width in convex, concave and straight facial profiles for Saudi, Indian and Bangladeshi nationals. Materials/methods: 114 subjects of each Saudi, Indian & Bangladeshi nationality were grouped into convex, concave and straight profile based on angle of convexity. Gingival zenith position (GZP) on #11 and #21 was evaluated on the scanned dental plaster model using CBCT. Inter and Intra group comparison was done using one-way ANOVA test. Results: Mean GZP values ranged from 0.84 mm to 1.10 mm, 0.75 mm to 1.02 mm and 0.87 mm to 1.14 mm for Saudi, Indian and Bangladeshi subjects respectively. Statistically significant (p < 0.05) difference was observed in convex, concave and straight profile subjects of these nationalities. Conclusion: GZP variation does exist in different facial profiles of Saudi, Indian & Bangladeshi nationalities with respect to central incisors. Clinical significance: These findings help clinician to consider facial profile as important entity in designing the smile following restorative and prosthetic procedures such as crown lengthening, teeth selection, implant esthetics and laminates. Keywords: Zenith, Facial profile, Esthetics